Closer vein spacing by ectopic expression of nucleotide-binding and leucine-rich repeat proteins in rice leaves - Lo, Shuen-Fang; Chatterjee, Jolly; Biswal, Akshaya K.; Liu, I.-Lun; Chang, Yu-Pei; Chen, Pei-Jing; Wanchana, Samart; Elmido-Mabilangan, Abigail; Nepomuceno, Robert A.; Bandyopadhyay, Anindya; Hsing, Yue-ie; Quick, William Paul (Springer, 2022)
Elevated expression of nucleotide-binding and leucine-rich repeat proteins led to closer vein spacing and higher vein density in rice leaves.To feed the growing global population and mitigate the negative effects of climate change, there is a need to improve the photosynthetic capacity and efficiency of major crops such as rice to enhance grain yield potential. Alterations in internal leaf morphology and cellular architecture are needed to underpin some of these improvements. One of the targets is to generate a “Kranz-like” anatomy in leaves that includes decreased interveinal spacing close to that in C4plant species. As C4photosynthesis has evolved from C3photosynthesis independently in multiple lineages, the genes required to facilitate C4may already be present in the rice genome. The Taiwan Rice Insertional Mutants (TRIM) population offers the advantage of gain-of-function phenotype trapping, which accelerates the identification of rice gene function. In the present study, we screened the TRIM population to determine the extent to which genetic plasticity can alter vein density (VD) in rice. Close vein spacing mutant 1 (CVS1), identified from a VD screening of approximately 17,000 TRIM lines, conferred heritable high leaf VD. Increased vein number inCVS1was confirmed to be associated with activated expression of two nucleotide-binding and leucine-rich repeat (NB-LRR) proteins. Overexpression of the twoNB-LRRgenes individually in rice recapitulates the high VD phenotype, due mainly to reduced interveinal mesophyll cell (M cell) number, length, bulliform cell size and thus interveinal distance. Our studies demonstrate that the trait of high VD in rice can be achieved by elevated expression of NB-LRR proteins limited to no yield penalty.